Comparative study of octane booster variations in pertalite on exhaust gas emissions of the K15B Engine - Supriadi; Wahyu Angga Restu; Fadhlah Sinurat (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The increasing number of vehicles powered by internal combustion engines in Indonesia has led to a corresponding rise in air pollution. This growing pollution poses significant environmental challenges and directly impacts public health. This study aims to reduce emissions produced by combustion engines, particularly the Suzuki K15B engine, through the application of various octane booster types added to Pertalite fuel (octane rating 90) at concentrations of 0.3%, 0.4%, and 0.5%. Exhaust gas emissions were measured using an Engine Gas Analyzer during the use of both pure Pertalite and Pertalite blended with octane boosters. Each composition was tested three times to ensure data accuracy and reliability. The results revealed that the greatest reduction in carbon monoxide (CO) concentration occurred with a 0.4% addition of Octane Prime, where CO levels decreased from 0.5% to 0.013%. Meanwhile, the most significant reduction in hydrocarbon (HC) emissions was observed with a 0.3% Octane Prime addition, lowering HC levels from 265 ppm to 60.7 ppm. Based on these findings, it can be concluded that the appropriate use of octane boosters in Pertalite fuel effectively reduces exhaust gas emissions from combustion engine vehicles